Automated image caption generator in Bangla using multimodal learning - Rodoshi, Mashiat Hasin; Ahmed, Moin Uddin; Ashraf, Md. Sobhan; Mim, Md. Galib Hasan; Khanam, Ashfia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.